Anti-inflammatory Limonoids From Cortex Dictamni - Chen, Yue; Ruan, Jingya; Sun, Fan; Wang, Huimei; Yang, Shengcai; Zhang, Ying; Yan, Jiejing; Yu, Haiyang; Guo, Yuanqiang; Zhang, Yi; Wang, Tao (Frontiers in Chemistry, 2020)
The root barks of perennial herb Dictamnus dasycarpus (Cortex Dictamni) were reported to be rich in anti-inflammation activity constituents, limonoids. Then, the investigation of anti-inflammation therapeutic limonoids from this plant was developed in the present study. Through the combination of various chromatographies isolation, six new limonoids, named dictamlimonol A (1), dictamlimonoside B (2), and dictamlimonols C–F (3–6), along with seven known ones (7–13), were obtained. Their structures were ascertained based on the extensive spectroscopic methods and ECD data analysis. Among them, compound 1 was the first 7,19-epoxy limonoid found in natural products. The anti-inflammatory effects of all limonoids were evaluated in lipopolysaccharide (LPS)-treated RAW 264.7 cell lines. Compounds 5, 7–11, and 13 were found to inhibit LPS-induced nitric oxide (NO) production. Moreover, dictamlimonol D (5), fraxinellone (11), and dasylactone A (13) were found to reduce the LPS-induced expressions of interleukin-6 (IL-6), tumor necrosis factor (TNF-α), inducible nitric oxide synthase (iNOS), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and cyclooxygenase-2 (COX-2) at the protein levels in a dose-dependent manner. These findings support that the administration of Cortex Dictamni may be beneficial for inflammation.